Parametric Study on the Effect of Water Viscosity to the Soil Matric Suction - Guna Saigaran, Saranya; Abu Talib, Zaihasra (Recent Trends in Civil Engineering and Built Environment, 2024)
Matric Suction of soil is the negative pore water pressure of the soil. Numerous factors are act as the inducing factors to the matric suction in the soil. Water quality is one of the main factors that influence the soil’s matric suction which can be affected by different water quality parameters. Viscosity of water is a prime elements in altering the action of matric suction when the soil is saturated with the different viscosities of water. This study is to determine the matric suction with controlled sample (rainfall) and different water viscosity and also aims to identify and compare the relationship between matric suction of soil with different water qualities (viscosity,cP). The method applied in this study to determine the matric suction using Tensiometer. The alteration of different viscosity of saltwater is conducted through the variation of different concentration of salinity. The viscosity is obtained through the Vertical Falling Sphere Method. The analysis of data indicates that the different viscosity of the water influenced by the level of salinity shows the different level of action of matric suction. This concludes that when the viscosity of water is increasing, the matric suction of the soil decreases. The higher viscosity induced the matric suction of soil which is the negative pore water pressure of the soil becomes lower.